Вдосконалення інструментів іпотечного житлового ринку України - Кондрашова, Г.П. (Культура народов Причерноморья, 2014)
На сучасному іпотечному ринку житла України використовуються різноманітні
інструменти.
Найбільш повну класифікацію інструментів іпотечного ринку житла було надано в дослідженнях
Любуня О.С., Кірєєва О.І., Домрачева В.М. та інших авторів. З їх точки зору, інструменти іпотечного
ринку житла можуть бути класифіковані у кілька основних груп. Це фінансові інструменти
акумулювання ресурсів на цілі іпотечного житлового кредитування; іпотечні кредити як інструменти
іпотечного фінансування; інструменти забезпечення іпотечних кредитів та їх сек'юритизації;
інструменти державного регулювання іпотечного ринку житла тощо.
В статті проаналізовано сучасні інструменти іпотечного житлового ринку України, виявлені основні
проблеми їх функціонування та напрями вдосконалення. На современном ипотечном рынке жилья Украины используются разнообразные
инструменты.
Наиболее полная классификация инструментов ипотечного рынка жилья была предоставлена в
исследованиях Любуня О.С., Кірєєва О.І., Домрачева В.М. но других авторов. С их точки зрения,
инструменты ипотечного рынка жилья могут быть классифицированы в несколько основных групп.
Это финансовые инструменты аккумулирования ресурсов на цели ипотечного жилищного
кредитования; ипотечные кредиты как инструменты ипотечного финансирования; инструменты
обеспечения ипотечных кредитов и их секъюритизации; инструменты государственного регулирования
ипотечного рынка жилья и т.д.;
В статье проанализированы современные инструменты ипотечного жилищного рынка Украины,
выявлены основные проблемы их функционирования и направления совершенствования. At the modern mortgage market the accommodations of Ukraine are used various instruments.
The most complete classification of instruments of mortgage market of accommodation was given in researches
of Lubunya O., Кіreeva O.I, Domracheva V.M. but other authors. From their point of view, the instruments of
mortgage market of accommodation can be classified in a few basic groups. It is financial instruments of
accumulation of resources on the aim of the mortgage housing crediting; mortgage credits as instruments of the
mortgage financing; instruments state providing of mortgage loans and them secutirization; to pieces
instruments adjusting of mortgage market of accommodation; instruments of state stimulation of the mortgage
housing crediting and aspiration of economies of population are on investment aims; instruments research and
information го providing of participants of mortgage market of accommodation.
The effective functioning of instruments of mortgage housing market brings к over of more successful realization
of the housing mortgage programs. Development of new and perfections of functioning of existent instruments of
mortgage housing market of Ukraine are transformed in the substantial factor of increase of efficiency of
realization of the mortgage housing programs in Ukraine. The modern instruments of mortgage housing market
of Ukraine are analysed in the article, the basic problems of their functioning and directions of perfection are
educed.